More than 170 polyunsaturated tocopherol-related compounds in a vitamin E capsule: Countercurrent chromatographic enrichment, gas chromatography/mass spectrometry analysis and preliminary identification of the potential artefacts - Hammann, Simon; Kröpfl, Alexander; Vetter, Walter (Journal of Chromatography A, 2016)
Tocopherols and tocotrienols (usually summed up as vitamin E) are a class of structurally related natural antioxidants. Commonly, only some of the eight classic representatives (four tocopherols and four tocotrienols) are found with varied composition in food. In this study we fractionated 230 mg oil from commercial vitamin E supplement capsules by countercurrent chromatography (CCC) and subsequent analysis by gas chromatography with mass spectrometry (GC/MS) of silylated CCC fractions showed that these eight isomers represented only about 70% of total tocopherol compounds. Detailed analysis enabled the detection of 161 T3 isomers (α-, γ- and δ-T3) along with 18 tetra- and several penta-unsaturated isomers (tocools), two tocomonoenol isomers, and several degradation products with shorter isoprenoid side chain (apo-tocools). Altogether, over 170 tocool compounds, most likely artefacts which originated from an inappropriate oil refining process were described in this study. Silver ion high performance liquid chromatography (Ag+-HPLC) was used to separate one fraction rich in γ-T3 into four peaks each consisting of at least five peaks according to GC/MS. About ten γ-T3 isomers were also detected in rice bran oils from one producer bought retail in Germany.
Keywords: Countercurrent chromatography; Tocomonoenol; Tocotrienol; GC/MS; Rice bran oil; Vitamin E capsule